Епідеміологічні аспекти захворюваності на карієс та особливості розвитку карієсогенної ситуації в дітей із бронхіальною астмою - Возний, Олександр Вікторович; Шумна, Таміла Євгенівна; Лепетченко, Єлизавета Станіславівна; Vozniy, O. V.; Shumna, T. Ye.; Lepetchenko, Ye. S. (My University, 2018)
Мета роботи – провести аналіз спеціалізованої наукової літератури для узагальнення даних про сучасний підхід до профілактики і лікування карієсу та його ускладнень, а також стану стоматологічного здоров`я дітей з бронхіальною астмою. Матеріали і методи. Проаналізували і вивчили доступну наукову літературу за останні роки, присвячену особливостям поширеності стоматологічних хвороб, профілактиці та лікуванню карієсу і його ускладнень, а також стану стоматологічного здоров`я дітей із бронхіальною астмою. Висновки. Аналіз літературних джерел, а також власні дослідження продемонстрували необхідність глибшого вивчення представленої проблеми і розробки специфічної програми профілактики карієсу та його ускладнень у дітей із бронхіальною астмою. Tooth decay is the most important early age children problem of the health of the oral cavity. It is medical and social problem of many developed countries and countries with transitional economy. According to WHO, in some countries the frequency and the intensity of dental caries decrease, however the same indexes in Ukraine increase rapidly and systematically. The interconnection of dental diseases and general somatic pathology is known well and it occupies one of the leading places amongst the main reasons of dental caries. The occurrence of bronchial asthma among child population varies from 1% till 18%. Therefore, children with the diseases of respiration organs have higher marks of caries lesions than healthy children. The aim of the work is to carry out the analysis of the specialized scientific literature for the data generalization on the modern looks on the prophylaxis and treatment of dental caries, its complications and the condition of dental health in children with bronchial asthma. Materials and methods. We have studied and analyzed the scientific literature available in the last years, which is devoted to the peculiarity of prevalence of dental diseases, prophylaxis and treatment of tooth decay, its complications and the condition of dental health in children with bronchial asthma. There are different indexes of caries prevalence and intensity in Ukraine according to our research. Thus, in the western regions the prevalence comes up to 93-100% and intensity 3,4-6,5, whereas in the central and south-east regions the same marks are up to 73-93% and 2,0-4,3. There is a huge influence on the caries prevalence by genetic tendency, attendant somatic pathology, social and hygienic factors. It is known that patients with bronchial asthma use inhalation glucocorticosteroids as basic treatment. This fact places them into the group of higher risk of caries development. But the influence of these drugs on the progress of tooth decay and saliva secretion is not studied well. Scientists confirm that the use of inhalation glucocorticosteroids can change chemical and immune compound of oral liquid (decrease saliva secretion speed, pH, number of calcium, phosphor, lysozyme and the raise of saliva viscosity). All these changes along with decrease of Ig A and ptyalin amount makes these children defenseless to caries and assists in development of cariogenic situation in the oral cavity. Moreover, children with allergic pathology have changes of immune reactivity and dysfunction of albumen and mineral exchange. At the same time the lesion of hard tissues of teeth in children with hypoxia which is determined as inborn and heritable diseases most often appear as the systemic hypoplasia in combination with plural caries. Caries prevalence in children with bronchial asthma is about 88-89% according to the latest news. We need also to draw attention to the changes of the osseous tissue. It depends not only on burden and duration of bronchial asthma, but also on the peculiarity of progression of caries process. These children have low mineral density and modified indexes of mineral and bone exchanges. All this facts confirm the systemic character of the bone lesion in these patients. Therefore, the rate of alterations grows up proportional to intensity of tooth decay. Conclusions. Thus, the analysis of the data, as well as our own research, have demonstrated the necessity of study of described problem and elaboration of specific prophylaxis program of dental caries and its complications in children with bronchial asthma more deeply.
The epidemiological aspects of caries spreading and the peculiarity of development of cariogenic situation in the children with bronchial asthma
Keywords: карієс; бронхіальна астма; глюкокортикостероїди; dental caries; bronchial asthma; glucocorticosteroids